2018
DOI: 10.3389/fimmu.2018.00856
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immune- and Stress-Related Transcript Response Induced by Air Exposure and Vibrio anguillarum Bacterin in Rainbow Trout (Oncorhynchus mykiss) and Gilthead Seabream (Sparus aurata) Mucosal Surfaces

Abstract: Fish have to face various environmental challenges that may compromise the efficacy of the immune response in mucosal surfaces. Since the effect of acute stress on mucosal barriers in fish has still not been fully elucidated, we aimed to compare the short-term mucosal stress and immune transcriptomic responses in a freshwater (rainbow trout, Oncorhynchus mykiss) and a marine fish (gilthead seabream, Sparus aurata) to bacterial immersion (Vibrio anguillarum bacterin vaccine) and air exposure stress in skin, gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 90 publications
8
63
1
Order By: Relevance
“…Stressors affect the activation of hypothalamus-pituitary-interrenal axis (HPI) in different organs, which is involved in immune and stress response in different species of teleost. Studies showed that although most fishes exhibit a general stress response, the pattern and magnitude of the response may be influenced by environmental factors such as ammonium, temperature, and salinity [75,76]. Similar to the results of our control setup, cortisol levels were previously found to be increased, and immune responses were decreased in changing or stressful conditions for aquatic species [8,54,72].…”
Section: Discussionsupporting
confidence: 87%
“…Stressors affect the activation of hypothalamus-pituitary-interrenal axis (HPI) in different organs, which is involved in immune and stress response in different species of teleost. Studies showed that although most fishes exhibit a general stress response, the pattern and magnitude of the response may be influenced by environmental factors such as ammonium, temperature, and salinity [75,76]. Similar to the results of our control setup, cortisol levels were previously found to be increased, and immune responses were decreased in changing or stressful conditions for aquatic species [8,54,72].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, SGR values of gilthead sea bream fed both control (2.1 ± 0.07% BW/day) and the EOs supplemented diet (2.03 ± 0.01% BW/day) compared favourably to those reported by Mongile et al 40 for this species also reared under summer conditions (1.5 ± 0.1% BW/day). Gills are one of the main mucosal immune barriers in fish 22,41,42 , but they also represent an ideal site for the attachment of ectoparasites 43 , potentially inducing a host hypometabolic response, as suggested for S. chrysophrii infections 44 . In fact, gills are considered one of the most active tissues in the protein synthesis with a significantly high plasticity in protein metabolism 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Gills are one of the main mucosal immune barriers in fish 22 , 41 , 42 , but they also represent an ideal site for the attachment of ectoparasites 43 , potentially inducing a host hypometabolic response, as suggested for S. chrysophrii infections 44 . In fact, gills are considered one of the most active tissues in the protein synthesis with a significantly high plasticity in protein metabolism 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In teleosts, gill is the first organ that responds to rapid changes in the DO level of water. Hypoxia disrupts the normal functions of the gill, including osmoregulation, respiration and nitrogenous waste excretion [28]. Therefore, the study about transcriptome response to hypoxia stress in gill tissue has significance.…”
Section: Degs As Adaptive Response To Hypoxiamentioning
confidence: 99%